"Het Masker". - Fleerackers, Johan; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1988)
Buggenhout, Rene ; De Bolle, Francis ; De Vis, Etienne ; Ketele, Alexander ; Landuyt, Octave ; Leclercq, Guy ; Leon, Eric ; Minnaert, Frans ; Reniere, Paul ; Somville, Roger ; Van Kerckhoven, Imelda ; Vervisch, Godfried
"Het Masker", Hof ter Nederloo, Sint-Pieters-Leeuw, 14 mei - 26 juni 1988
boek